Green Sana’a and the Yemeni Landscape: Environmental Poetics of Abdulaziz Al-Maqaleh - Hamoud Yahya Ahmed Mohsen; Ruzy Suliza Hashim; Raihanah M.M. (Asiatic: IIUM Journal of English Language and Literature, 2022)
Ecocriticism investigates the link between literature and the natural world. It has received scant attention in the Arabic literary tradition, notably in the Yemeni canon. Using ecocriticism and environmental poetics, this article analyses selected modern Yemeni poetry of Abdulaziz Al-Maqaleh and assesses the extent to which an ecological link exists between the persona and the geography of his homeland, Yemen. The findings suggest a duality of visualisations that contribute to the poet’s environmental vision. The first vision is tangible, evidenced by his transfer from his birthplace to Cairo. The second is emotional that evokes contemporary sensitivity to ecology and sustainability, environmental challenges, and the links between nature and culture that have become obvious in current literary studies worldwide. His exile experience prompts the depiction of his deep environmental ties to Yemen. It is reflected in the various facets of Sana’a’s green environment, which reflect the ardent hope of numerous people whose physical, mental, and emotional perspectives have been eradicated or lost as a result of being displaced from their homelands.